A new functional model for determining minimum and maximum detectable deformation gradient resolved by satellite radar interferometry - Baran, Ireneusz; Stewart, Michael; Claessens, Sten (IEEE Geoscience and Remote Sensing Society, 2005)
In this paper, a functional model for determining the minimum and maximum detectable deformation gradient in terms of coherence for synthetic aperture radar (SAR) sensors is presented. The model is developed based on a new methodology that incorporates both real and simulated data. Sets of representative surface deformation models have been simulated, and the associated phase from these models introduced into real SAR data acquired by European Remote Sensing 1 and 2 satellites. Subsequently,interferograms were derived, and surface deformation was estimated. A number of cases of surface deformation with varying magnitudes and spatial extent have been simulated. In each case, the resultant surface deformation has been compared with the "true" surface deformation as defined by the deformation model. Based on these comparisons, a set of observations that lead to a new functional model has been established.Finally, the proposed model has been validated against external datasets and proven viable. Although the major weakness of the model is its reliance on visual interpretation of interferograms, this model can serve as a decision-support tool to determine whether or not to apply satellite radar interferometry to study a given surface deformation.